Single muscle fibre biomechanics and biomechatronics – The challenges, the pitfalls and the future - Friedrich, Oliver; Haug, Michael; Reischl, Barbara; Prölß, Gerhard; Kiriaev, Leon; Head, Stewart I.; Reid, Michael B. (International Journal of Biochemistry and Cell Biology, 2019)
Interest in muscle biomechanics is growing with availabilities of patient biopsies and animal models related to muscle diseases, muscle wasting (sarcopenia, cachexia), exercise and drug effects. However, development of technologies or facilitated systems required to measure biomechanical and contractile properties of single fibres has not kept pace with this demand. Most studies use manual mechatronics systems that have not changed in decades and are confined to a few labs worldwide. Available commercial systems are expensive and limited in versatility, throughput and user-friendliness. We review major standard systems available from research labs and commercial sources, and benchmark those to our recently developed automated MyoRobot biomechatronics platform that provides versatility to cover multiple organ scales, is flexible in programming for active/passive muscle biomechanics using custom-made graphics user interfaces, employs on-the-fly data analyses and does not rely on external research microscopes. With higher throughput, this system blends Industry 4.0 automation principles into myology.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Biomechatronics; Biosensors; Myorobotics; Single fibre; Skeletal muscle